Dimensi Spiritual dalam Kepemimpinan - Arcadius Benawa (Bina Nusantara University, 2014)
This article aims to show that the spiritual aspect must be noted in the leadership because every leader is always marked with oath of office in carrying out her/his position. So, how leaders are accountable, it is not only on the horizontal level but also at the vertical level. Research was done with phenomenological and literature studies about the practice of leadership faced with a number of theories about leadership and then to be synthesized the more authentic leadership than just imaging or false branding leadership. This article was based on the assumption that leadership (including in the political sphere) was merely a sociological problem that kicked out spiritual aspects, while in the historical development of leadership, it had never been excluded from the spiritual dimension, whether in the form of manipulative (just because fed people understand that leadership came from the “sky”/gods). So then, a king acted tyrannical and led to the birth of authentic leadership as popularized as servant leadership. This article concluded that authentic leadership will give more benefit to develop the life system as well as the purpose of leadership itself rather than a merely apparent leadership which actually hurts the members (people) because of the failure to meet the expectations of the members (people).